Preparation and performance of a pH-sensitive cisplatin-loaded magnetic nanomedicine that targets tumor cells via folate receptor mediation - CHEN, SHUAI-JUN (Mol Med Rep, 2016)
The present study aimed to prepare cisplatin (CDDP)-loaded magnetic nanoparticles (MNPs), which target folate receptors via a pH-sensitive release system (FA-PEG-NH-N=MNPs-CDDP). This is of interest for the development of intelligent drug delivery systems that target tumors of the head and neck. The chemical coprecipitation method was used to prepare ferroferric oxide MNPs. These were modified with aldehyde sodium alginate complexed with the chemotherapeutic agent, CDDP on the surface of the nanoparticles. Double hydrazine-poly(ethylene glycol; PEG) was also prepared by attaching the carboxyl group of hydrazine-folate on one side of the double hydrazine-PEG, obtaining folate-hydrazine-PEG-diazenyl. This binds the aldehyde group of sodium alginic acid on the MNP to enclose CDDP, in order that it is sequestered within the carrier. This method obtained a pH-sensitive, FA-modified CDDP-loaded MNP (FA-PEG-NH-N=MNPs-CDDP), which acts as an intelligent tumor targeting drug delivery system. The mean size of the MNPs was ~10.2±1.5 nm, the mean hydrodynamic diameter detected by laser particle sizing instruments was 176.6±1.1 nm, and the ζ-potential was −20.91±1.76 mV. The CDDP content was 0.773 mg/ml, the iron content was ~1.908 mg/ml and the maximum saturation magnetization was 16.3±0.2 emu/g. The current study produced a pH-sensitive FA-modified CDDP-loaded MNP that is stable and exhibits magnetic responsiveness, which releases CDDP in a low pH environment.